Libraries: Transforming the Educational Process through Total Quality Management (TQM) in Akwa Ibom State (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The overall purpose of this study was to examine Libraries: transforming the educational process through total quality management (TQM) in Akwa Ibom State. Descriptive survey research design was adopted for the study and it was conducted in Akwa Ibom State. The target population for the study comprised all librarians in public secondary schools in Akwa Ibom State. Simple random sampling technique was used to select 54 librarians drawn from public secondary schools in Akwa Ibom State. Also, 20 other librarians were also randomly selected for the study. This gave a total of 74 respondents used for the study. The instrument used for data collection was a questionnaire titled “Libraries and Transformation of Educational Process Questionnaire (LTEPQ)”. Face and content validation of the instrument was carried out by an expert in test, measurement, and evaluation in order to ensure that the instrument has the accuracy, appropriateness, and completeness for the study under consideration. The researcher subjected the data generated for this study to percentage analysis technique meant to answer the research questions. Based on the study it was concluded that Throughout the last few decades, technological breakthroughs have altered the working patterns of libraries and information centers. The traditional image of the Library and its professionals has also changed. Due to the changing needs of users, information professionals are expected to prepare themselves with developing concepts. TQM guides the identification of productive growth in the academic environment. One of the recommendations made was that Librarians should be given adequate training on effective library operations and manipulation with Total Quality Management in mind in order to motivate the users for constant utilization of the libraries, irrespective of the type.